Animal Health Service Delivery in Crop-Livestock and Pastoral Systems in Ethiopia - Gizaw, Solomon; Woldehanna, Mengistu; Anteneh, Habtamu; Ayledo, Gewado; Awol, Fasil; Gebreyohannes, Gebreegziabher; Gebremedhin, Berhanu; Wieland, Barbara (Frontiers in Veterinary Science, 2021)
We characterize the animal health service delivery system in Ethiopia using five questionnaire surveys involving 4162 livestock keepers. Livestock keepers’ access to, use of and satisfaction with animal health services significantly varied across livestock production systems, geographic locations, socioeconomic strata, and service providers. Livestock keepers in crop-livestock and agropastoral systems had 5.5 (odds ratio = 5.453, P = 0.000) and 2.5 (odds ratio = 2.482, P = 0.000) times more access to services in reference to the pastoral system. In reference to private veterinary clinics, livestock keepers reported higher access to services provided by all the other service providers, particularly to services provided by extension agents, drug shops and CAHWs. Similarly, better access was reported by male than female and wealthier than poorer farmers and pastoralists. In general, low access to services was reported, ranging 19.3% to 32.7% across livestock systems. Effective demand, measured in number of visits to service providers and health expenditures, was higher by the highland farmers than pastoralists (odds ratio = 2.86; P = 0.000). Wealth, gender and age also had significant effects on effective demands. Satisfaction with services was evaluated on availability (av), accessibility (ac), quality (qw), and timeliness (tm) of services. Principal component analysis was conducted to derive the latent variable ‘satisfaction’ from the four measures, extracted only one factor, indicating the four variables are measuring the same construct (satisfaction). There was a significant dissatisfaction with the public sector, with average scores of 0.06 and 0.19 for the public and private service providers, respectively. We conclude that livestock keepers in remote regions, pastoralists, women, poorer, and older livestock keepers have less access and satisfaction with services. We recommend an integrated, multi-sectoral involvement to improve the veterinary service delivery through improved veterinary infrastructure, public-private partnership, and animal health information system across the various livestock production systems.